Study the alkaloid composition in the rue (Thalictrum foetidum), occurring in Karkaralinsk region - Zhumagalieva, Zh.Zh.; Yeleupaeva, Sh.K.; Korchyn, V.I. (Fundamental and Experimental Biology, 2016)
The paper studied the plant (Thalictrum foetidum) (vaslistnika) collected Қarkaralinskikom district of Karaganda region in the flowering stage. Aerial parts of the plant rue (Thalictrum foetidum) by chloroform extraction amount received extractives. Identification alkaloids conducted TLC. Structures of isolated alkaloid glaucine identified using modern physical and chemical methods and IR, PMR-spectra. 13C NMR spectra were recorded on spectrometers Vruker AC 200 [working frequency 200.13 (1H) and 50.32 MHz (13C)].